A Model of Integrated Passenger Transport System in a Specific Region - Peter Faith (Communications - Scientific letters of the University of Zilina, 2002)
Paper reports on basic principles in development of integrated transport systems in the region. It explains reasons why integration of mass passenger transport is necessary, as well as procedures of its realization with presentation of economic, legislative and organizational measures.Everything what IDS brings are new, advanced organizational and economic relationships between subjects which participate in mass passenger transport either as passengers, transport operators, or districts, regions, towns, villages or the state.